Comparative analysis of plantar pressure distribution among football players across playing positions: A cross-sectional study - Arif Pristianto; Anindya Maghfira Zain; Farid Rahman; Pungki Indarto; Anugrah Nur Warthadi (Physical Education and Sports: Studies and Research, 2026)
Background: Football players exhibit different muscle activation patterns during different playing activities, which can affect plantar pressure on the feet. Uneven, unbalanced plantar pressure distribution can cause muscle tension, leading to musculoskeletal injuries in the feet. Objectives: This study aims to determine and compare plantar pressure distribution among football players based on playing position. Methods: This study is an analytical observational study using a cross-sectional approach. The sample in this study consisted of 24 football players aged 15-18 years who met the inclusion criteria. Plantar pressure was measured using a Zebris Force Distribution Measurement (FDM) platform on the forefoot and rearfoot areas. Statistical analysis included normality tests (Shapiro-Wilk) and multivariate tests (ANOVA) according to data distribution. Results: Differences in plantar pressure were observed between defenders, forwards, and strikers in static conditions (p < 0.05), but not in dynamic conditions (p > 0.05). Conclusions: This study shows differences in plantar pressure distribution among football players in defender, forward, and striker positions under static conditions. However, under dynamic conditions, no significant differences were found among playing positions.